Representações interculturais de gênero no romance A república dos sonhos, de Nélida Piñon - Lúcia Osana Zolin (Estudos de Literatura Brasileira Contemporânea)
Brazilian author Nélida Piñon's novel A república dos sonhos (The Republic of Dreams) (1984) engages, on the one hand, gender representations of a medieval- inspired Galicia, with its oral traditions, pilgrimages and emigrants. On the other hand, the gender representations in 20th century Brazil provide a highly interest view of female emancipation brought about by feminist movements. The novel re- veals the process of discordant voices with regard to hegemonic ideologies such as patriarchy and phallogocentrism commonly represented and replicated in canoni- cal literature. Instead of the traditional feminine identity characterized and fixed by patriarchy-established gender female roles, she inscribes multiplicity and het- erogeneity. In other words, the decentralization of identities intersects with other issues such as race, ethnicity, class and sexual orientation as constitutive of the contemporary Brazilian society. Foregrounded on concepts from critical feminism and post-structuralism, a discussion ensues on the way a contemporary Brazilian female writer, dialoging with Spanish tradition, represents feminine identities and gender relationships in this important 20th century novel.